IMPROVING THE UNDERSTANDING OF CONTENT ON READING FOR TOEFL THROUGH YOUTUBE VIDEOS - Sumardiono, Luqman Al Hakim (Widya Wacana: Jurnal Ilmiah, 2019)
The study aims at describing the use of video based on global view on education in reading for TOEFL lesson to improve the students’ reading skill and to internalize the values of mental revolution for the students of English education program at Universitas Slamet Riyadi. The research method is a collaborative action research. There are four phases in conducting the research: planning, action, observation, reflection, and revising the plan. The subject of the research is 2nd and 4th semester students of English education program at Universitas Slamet Riyadi, however in this article,the writers intend to describe the findings on reading for TOEFL lesson (4th semester). The techniques in collecting the data are observation, questionnaire, and document analysis. Meanwhile, the techniques in analyzing the data are qualitative and quantitative analyses. The qualitative data analysis consists of data data reduction, data display, and drawing conclusion. And the quantitative data analysis is through mean score in every cycle. Research findings show that in the reading for TOEFL lesson, the mean score for pre-test was 38.7. It was improved become 72.5 in the 1st cycle. Finally, in the 2nd cycle, the meanscore was 73.2. Meanwhile, another finding in terms of internalizing the values of mental revolution was that the students are able to find and conceive the values found in the videos and the texts, such as professionalism, creativity, working together, and nationalism values. Key words: Collaborative Action Research, Reading for TOEFL, Mental Revolution.